Determinants of turn-up for HIV care among lactating mothers with infants at Panyadoli Health IV, Kiryandongo district. A cross-sectional study. - Tusiime, Rebecca; Nansereko, Hasifa; Naggulu, Immaculate Prosperia; Nalubega, Jane Frank (Student's Journal of Health Research Africa, 2025)
Background In Uganda, the impact of low turn-up on Lactating mothers with Infants is significant, as delays in ART adherence increase maternal viral load by 20%. The purpose of the study was to assess the Determinants of Turn-Up for HIV Care among Lactating Mothers with Infants at Panyadoli Health IV, Kiryandongo District. Methods A descriptive cross-sectional study design employing quantitative methods of data collection was conducted at Panyadoli Health IV, Kiryandongo District. In a duration of 5 days, 45 lactating mothers were selected using a simple random sampling method. A structured questionnaire was used to collect data, consisting of closed-ended questions. The data collected was analyzed manually, and findings were entered into a Microsoft Excel 2013, which was then presented in the form of tables, pie-charts, and graphs. Results The Majority of the respondents, 24(53%), were 18-30 years old. Less than half of the respondents, 16(36%), had secondary education. More than half of the respondents, 26(58%), were married, on individual determinants; 73% of mothers lacked partner support, 84% experienced stigma, 45% cited caregiving duties as a barrier to clinic attendance, and the majority 62% faced challenges due to pre-existing infant health conditions. Health facility-related determinants included lack of appointment reminders (73%), medication stock-outs (80%), and judgmental attitudes from health workers (58%). Socio-economic determinants included long distances to clinics (47%), high medication costs (67%), transport challenges (56%), and lack of support systems (51%). Conclusion Lack of partner support, stigma, caregiving responsibilities, medication stock-outs, long distances to clinics, and negative health worker attitudes were key factors affecting ART clinic attendance among lactating mothers with infants. Recommendation There is a need to strengthen partner and community support systems, improve drug availability, implement effective reminder systems, address stigma and staff attitudes, education, and advocacy to enhance ART adherence among lactating mothers.